VD_FINDINFO Jug / 2017 / 106 vom 28. April 2016 - VD Tribunal cantonal (2016)
RÉVISIONDÉCISION, DÉCISION D'IRRECEVABILITÉ, ORDONNANCE PÉNALE | 410 al. 1 let. a CPP (CH), 411 CPP (CH), 412 al. 2 CPP (CH)